CULTURA RESPONSABILIZĂRII CADRELOR DIDACTICE - O EXIGENŢĂ ACTUALĂ - USM ADMIN (Moldova State University, 2008)
Nowadays there is accepted the idea that the establishment of didactic staff responsibilisation culture is up to date and very promising. The explanation is fairly simple: if everybody is answerable for field of activity then education quality will not be such an arguable field. The credibility in the magical power of the didactic staff responsibilisation is not defended yet. Which are the causes? Is responsibilisation of the didactic staff only a notion in vogue?